2019
DOI: 10.3151/jact.17.79
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance and Durability of Latex-Modified Fiber-Reinforced Concrete

Abstract: In this study, the mechanical performance and durability of latex-modified fiber-reinforced concrete were experimentally investigated. For these purposes, various types of tests were carried out: compressive, flexural, restrained drying shrinkage, water-tightness, and freeze and thaw tests. In total, 59 test specimens were manufactured and performed in this study. The latex weight fractions of 10, 15, and 20% and the fiber volume fractions of 0.2 and 0.3% were used as main test parameters. For each fiber volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In the process of freeze-thaw cycle, the water in the pores of porous materials will produce the transformation of the liquid phase and the gas phase. The heat conduction equation of water phase's latent heat is as follows [15]:…”
Section: Governing Differential Equations Of Freeze Thaw Cyclesmentioning
confidence: 99%
“…In the process of freeze-thaw cycle, the water in the pores of porous materials will produce the transformation of the liquid phase and the gas phase. The heat conduction equation of water phase's latent heat is as follows [15]:…”
Section: Governing Differential Equations Of Freeze Thaw Cyclesmentioning
confidence: 99%
“…In another study, Truong et al [14] reported that the use of 15% polymer improved the compressive strength at an early age, with a 91% ratio of compressive strength at day 7 to that of day 28. Additionally, the time until the development of cracks was delayed, and the final crack value was reduced.…”
Section: Introductionmentioning
confidence: 96%
“…Preventive measures must be implemented to improve the longevity of concrete pavements and structures and improve the life cycle performance. Latex based polymeric materials are added to concrete to improve its performance in particular applications for increasing its resilience and durability [1], [2], [3]. The use of tailor-made synthetic rubber latex in major infrastructure projects is widely accepted.…”
Section: Introductionmentioning
confidence: 99%